2021
DOI: 10.1155/2021/7532583
|View full text |Cite
|
Sign up to set email alerts
|

Fractures around Trochanteric Nails: The “Vergilius Classification System”

Abstract: Introduction. The fractures that occurred around trochanteric nails (perinail fractures, PNFs) are becoming a huge challenge for the orthopaedic surgeon. Although presenting some specific critical issues (i.e., patients’ outcomes and treatment strategies), these fractures are commonly described within peri-implant ones and their treatment was based on periprosthetic fracture recommendations. The knowledge gap about PNFs leads us to convene a research group with the aim to propose a specific classification syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…In recent years, four different classifications have been proposed for PIFs after intramedullary fixation of proximal femoral fractures [13,[15][16][17]. All classifications take into account the fracture location, whereas some include a description of the PIF morphology and/or initial fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, four different classifications have been proposed for PIFs after intramedullary fixation of proximal femoral fractures [13,[15][16][17]. All classifications take into account the fracture location, whereas some include a description of the PIF morphology and/or initial fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to surgeon perception of technical ease, several authors have shown that there is a learning curve associated with CN use 10,12 , and a high risk of complications (including perinail fractures) had been reported. These latter are an emerging entity with specific problems to face, which led some authors to purpose a specific classification system to guide treatment 51 . The most recent Cochrane review on the treatment of pertrochanteric fractures concluded that the SHS may be a superior construct because of a decreased rate of surgical complications compared with CN 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors hypothesized that a specific algorithm for PIFF could guide trauma surgeons in the difficult decision-making process, but these algorithms can be complex and confusing ( 12 ). Three classification systems have been proposed as an attempt to address the best treatment option ( 13 , 14 , 15 ). Vergilius classification system is focused on fractures around trochanteric nails ( 13 ).…”
Section: Introductionmentioning
confidence: 99%